Urgensi Pendaftaran Perjanjian Kawin Dalam Perspektif Kekuatan Akta Notaris Terhadap Pihak Ketiga - Anak Agung Ayu Desy Nadhira Putri; I Wayan Novy Purwanto (Jurnal Interpretasi Hukum, 2025)
To ensure the safety and security of both spouses, a marriage contract details the distribution of marital assets in a legally binding document.  Notarial deeds still lack the evidentiary strength of third-party marriage contracts, particularly in cases where the agreements are not filed with a marriage registrar, and this is particularly true in practice.  Article 1868 of the Civil Code and Article 15 of Law Number 2 of 2014 about the Position of Notary control the formal and material force of a notarial deed. However, in practice, this does not always align with society's expectations.  Examining the third-party legal ramifications of an unregistered marriage contract and the binding nature of a notarial deed in creating a marriage contract are the primary goals of this research.  Using a statutory and conceptual approach, this research employs normative law and employs qualitative analysis.  According to the study's findings, a notarial deed can be used as flawless evidence by the parties involved, but it lacks the authority to bind third parties unless it is registered with the Civil Registration Office or the Office of Religious Affairs.  Thus, as an expression of the concept of publicity, the registration of a marriage agreement is highly urgent in order to ensure legal certainty and protection for the husband and wife as well as any interested third parties.